Data integrity proof and secure computation based on elgamal algorithm and iris extraction in cloud storage - H. Abbdal Refish, Salah (International Journal of Engineering and Technology, 2019)
Storage servers may not be fully trusted in cloud storage. So, it is of critical importance for users to check whether the data stored are kept intact or not. In this paper, an efficient and secure integrity checking method based on iris feature extraction and Elgamal algorithm is presented. This method gives the cloud users more confidence in detecting any block that has been modified. Additionally, the proposed scheme supports data dynamics by employing Merkle Hash Tree (MHT), which is used to store the location of each data operation. Data dynamics include such data operations as block modification, insertion, and deletion. With the proposed method, provable data possession and remote integrity checking under secure computation are provided. The performance and security analysis show that the scheme is secure and can be practically used for cloud environments.Â Â